PENGARUH PENDIDIKAN KARAKTER DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS SMA NEGERI 5 PADANGSIDIMPUAN - Mhd. Nau Ritonga; Hanafi .; Nelmi . (Jurnal Education and Development, 2021)
This study aims to find out: 1) what is the picture of character education for class X SMA Negeri 5 Padangsidimpuan, 2) what is the picture of student motivation for class X SMA Negeri 5 Padangsidimpuan, 3) what is the picture of student learning outcomes for class X SMA Negeri 5 Padangsidimpuan, 4) whether there is a significant influence between character education and learning motivation on the learning outcomes of 5th grade Padangsidimpuan students. The time of the study was carried out for 3 months starting from February to April 2021. The research method used was a descriptive method. The population used in this study were students of class X SMA Negeri 5 Padangsidimpuan. The sampling technique used is a random sample of 30 students. Data collection techniques obtained by questionnaires and documentation. The data analysis technique used descriptive analysis and inferential statistical analysis. Based on the calculations obtained from the results of data processing using SPSS Software Version 25 the results of the character education variable (Variable X1) obtained a t-test index of 2.273 while t-table was 1.697 with a significant value = 0.031. And the results of data processing from the learning motivation variable (Variable X2) obtained a t-test index of 2.235 while t-table was 1.697 with a significant value = 0.034. So it can be seen that the significant value is smaller than (0.031 < 0.05) and (0.034 < 0.05). So it can be concluded that the hypothesis Ha is accepted. This means that there is a significant influence between character education and learning motivation on the learning outcomes of class X students of SMA Negeri 5 Padangsidimpuan.